The Effectiveness Of Recruitment Of Civil Services (Asn) In Increasing Performance Of Employees In The Performance Section Of The Province Of Bengkulu - Ariska, Yesi Indian; Yustanti, Nirta Vera (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The purpose of this study is to determine the impact of civil servant recruitment on improving the performance of Bengkulu Province civil servant employees. The method used in this study is a descriptive method using a qualitative approach. Data acquisition techniques were conducted by interviewing, observing, and recording documents related to the civil servant recruitment process carried out by Bengkulu local civil servants. The data acquired will be investigated and qualitatively analyzed for all the data collected, and an interview with Duncan's theoretical approach to stress, whose effectiveness can be seen in three indicators: goal achievement, integration, and adaptation Supported by the results of. The results of the field survey came to the correct conclusion as the implementation of labor recruitment carried out by local civil servants in the Bengkulu Province is more transparent and responsible.